Penerapan Bimbingan Kelompok Teknik Role Play dalam Meningkatkan Keterampilan Sosial Anak Didik Pemasyarakatan - Zaleha Aprilia; Suryati Suryati; Hartika Utami Fitri (Journal of Society Counseling, 2023)
Social skills are actions that actually occur in everyday life. This research is entitled "Application of Role Play Technique Group Guidance in Improving Social Skills of Correctional Students in Grade 1 LPKA Palembang". Social skills have a fairly important role which will help to be braver when in a new environment, can make it easier to interact and facilitate delivery in any case. This study aims to find out how the description of the social skills of Correctional Students in Class 1 LPKA Palembang and the Strategy of Applying the Role Play Technique Group Guidance in improving the social skills of correctional students in Class 1 LPKA Palembang. This research method uses qualitative research methods. The research subjects taken consisted of seven research subjects, namely Correctional Students at Class 1 Palembang LPKA who had poor social skills. In this case group guidance is presented to help the process of improving these social skills by using role play techniques. The application of role play technical group guidance in improving social skills has the desired results because after carrying out the group guidance process Correctional students who have poor social skills have increased quite a bit afterwards. Improving social skills through role play techniques is a process of learning through a role and then playing that role as a stimulus to thoughts and actions, so that unconsciously new social skills have been formed by themselves. So it can be concluded that the application of role play technique group guidance in improving social skills is quite effective in improving social skills in correctional students in grade 1 LPKA Palembang.